The Count of Monte Cristo (Mackin classics, ,, 2008)
Nominated as one of America's best-loved novels by PBS's The Great American Read A popular bestseller since its publication in 1844, The Count of Monte Cristo is one of the great page-turning thrillers of all time. Set against the tumultuous years of the post-Napoleonic era, Alexandre Dumas's grand historical romance recounts the swashbuckling adventures of Edmond Dantès, a dashing young sailor falsely accused of treason. The story of his long imprisonment, dramatic escape, and carefully wrought revenge offers up a vision of France that has become immortal. As Robert Louis Stevenson declared, "I do not believe there is another volume extant where you can breathe the same unmingled atmosphere of romance."
Chronology , Introduction , Further reading , Note on the text , Count of Monte Cristo , Notes.